2012
DOI: 10.1021/cg300975s
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization from Solutions Containing Multiple Conformers. 2. Experimental Study and Model Validation

Abstract: In this Article, the validity of a model derived for crystal growth rates and supersaturation for solids crystallized from solutions of materials containing multiple conformers is evaluated. A simple and straightforward method for determining crystal growth rates using FBRM and FTIR/ATR is utilized, which leads to a large amount of growth rate data from a single experiment. Supersaturation and crystal growth rate obtained experimentally were in good agreement with model predictions. In particular, data indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
(37 reference statements)
0
20
0
Order By: Relevance
“…Nowadays, in-process data mostly uses FBRM instrumentation [19][20][21] which measures only the chord length distribution which can be challenging to extract 'first-principles' face-specific kinetics [45].…”
Section: Overall Linear Growth Ratementioning
confidence: 99%
“…Nowadays, in-process data mostly uses FBRM instrumentation [19][20][21] which measures only the chord length distribution which can be challenging to extract 'first-principles' face-specific kinetics [45].…”
Section: Overall Linear Growth Ratementioning
confidence: 99%
“…For example, in some cases, nucleation yields that polymorph in which the molecules retain their predominant solution phase conformation. [24][25][26] However, the dominant conformation in solution may also differ from conformations within the resulting polymorph. 27,28 Additionally, low concentration solvent additives can serve as molecular templates to promote nucleation and influence polymorph selection.…”
Section: Introductionmentioning
confidence: 99%
“…Computation was performed for an isothermal anti-solvent crystallization of a substance, hereafter denoted A, which is present as two main conformations in solution. The constant of equilibrium between conformers at different temperatures for A was reported in a previous study [71] and solute integration factor for same substance was reported in [73]. The corresponding reduced constants, KR, and kRF are calculated and reported here in Figure 8.…”
Section: Crystal Growth Inhibition By the Wrong Conformermentioning
confidence: 93%
“…Crystal growth inhibition due to integration of the WC, Θ RF , can be computed using Equation (22) at different temperatures, T 1 and T 2 . k F is expected to vary NLT 1 and the experimental measurement of k F at two temperatures is sufficient to extrapolate a trend in the typical temperature range for crystallization of organic substances from solution [73]. The activation energy for solute integration, E a , is expected to vary in the typical range for small organic molecules: 5 to 25 kcal/mol [128][129][130] and K R can be determined from solubility measurements and/or NMR analysis [50].…”
Section: Of 24mentioning
confidence: 99%
See 1 more Smart Citation